A5.07 The role of immunologic and inflammatory factors in the risk of microvascular and macrovascular impairment development in systemic lupus erythematosus – preliminary data. (24th February 2016) - Fischer, K; Sawicki, M; Chamiak-Ciemińska, K; Stolarczyk, J; Winikajtis-Burzyńska, A; Milchert, M; Ostanek, L; Bobrowska-Snarska, D; Kapłon, Ł; Przepiera-Będzak, H; Walecka, A; Brzosko, I; et al.
Abstract : Background and objectives: Vascular disorders are a well recognised clinical problem in systemic lupus erythematosus (SLE). This preliminary study was designed to evaluate the association between cerebral circulation changes, carotid arteries involvement as well as nailfold capillaroscopy (NC) abnormalities and immunologic/inflammatory markers, classical atherosclerosis risk factors and organ involvement in SLEpatients. Materials and methods: The study was performed in 30 SLE patients. Bilateral transcranial doppler (TCD) monitoring over the middle cerebral arteries according to the criteria of the International Consensus Group on Microembolus Detection was performed using two 2-MHz probes of the pulsed Doppler system MultiDop-T Digital (DWL Compumedics). MRI scans of the brain were carried out using a 1.5-T scanner GE Discovery 450 (GE Healthcare). Detection of carotid stenosis was performed using 3D contrast-enhanced MR angiography. Carotid intima-media thickness (cIMT) was measured with B-mode ultrasound. NC was done using Zeiss device. More than 100 variables were taken into account including cytokines, inflammatory markers, autoantibodies, classical risk factors for atherosclerosis and selected organ manifestations. Statistical analysis was performed with chi 2 Yates, chi 2 Pearson, rank Spearman correlations tests and logistic regression analysis. Results: Factors which significantly correlated with analysed vascular changes including microemboli in TCD, ischaemic changes in MRI and NC abnormalities, were thrombocytopenia (r = 0.47, p = 0.01), C-reactive protein (CRP) (r = 0.51, p = 0.0039) and antiphospholipid antibodies (aPLs) (r = 0.55, p = 0.0015). There was significant association between vascular endothelial growth factor (VEGF) and IL-6 and high cIMT (r = 0.36, p = 0.0492, r = 0.41, p = 0.0239, respectively) as well as NC abnormalities, especially megacapillaries presence (r = 0.38, p = 0.0415, r = 0.42, p = 0.0226, respectively). Additionally, patients with changes in NC significantly more frequently were dyslipidemic (r = 0.56, p = 0.0015), hypertensive (r = 0.41, p = 0.0252) and unveiled high titers of anti-dsDNA (r = 0.37, p = 0.0492) and cardiac involvement (r = 0.38, p = 0.0441). There was also important positive correlation between cIMT and NC abnormalities (r = 0.40, p = 0.0300) as well as microemboli in TCD (r = 0.44, p = 0.0211). Finally, microemboli in TCD were associated with MRI ischaemic changes (r = 0.45, p = 0.0177). Conclusions: NC and cIMT provide the optimal protocol to screen SLE patients for cardiovascular risk. CRP, VEGF, IL-6, aPLs and anti-dsDNA seem to be crucial pathogenic factors in micro- and macrovascular impairment development in SLE. Patients with higher cIMT and aPLs should undergo TCD for cerebrovascular risk assessment.